Assessment of Sperm PAWP Expression in Infertile Men - Tanhaei, Somayeh; Abdali-Mashhadi, Solmaz; Tavalaee, Marziyeh; Javadian-Elyaderani, Soudabeh; Ghaedi, Kamran; Seifati, Seyed Morteza; Nasr-Esfahani, Mohammad H. (Urology Journal, 2019)
Purpose: The aim of this study was to evaluate expression of Post-Acrosomal WW Binding Protein (PAWP) in infertile men with low and high fertilization post ICSI and also globozoospermic men. Materials and Methods: Semen samples were collected from 18 infertile men with previously failed or low fertilization (< 25%) post ICSI, 10 men with high fertilization (>50%) post ICSI, 15 globozoospermic men, and 21 fertile individuals. Then, expression of PAWP was assessed at RNA with quantitative Real Time PCR. Results: Relative expression of PAWP in sperm was significantly (P < .05) lower in infertile men with globozoospermia (41.5 ± 5.7) or low fertilization rate (43.3±10.4) compared to fertile (138.8 ± 17.3)or men with high fertilization (211.6 ± 75.6). In addition, a significant positive correlation (r = 0.628; P = .001) was observed between percentage of fertilization with the relative expression of PAWP. Conclusion: Considering solid recent evidences regarding PLC? as the main sperm factor involved in oocyte activation, therefore co-localization of PLC? with PAWP in perinuclear theca may account for the above observation and it is likely that PAWP may have other functions and/or it may assist PLC?.